Morphometric Differences in Planum Temporale in Schizophrenia and Bipolar Disorder Revealed by Statistical Analysis of Labeled Cortical Depth Maps - Ratnanather, J. Tilak; Cebron, Shannon; Ceyhan, Elvan; Postell, Elizabeth; Pisano, Dominic V.; Poynton, Clare B.; Crocker, Britni; Honeycutt, Nancy A.; Mahon, Pamela B.; Barta, Patrick E. (Frontiers in Psychiatry, 2014)
Differences in cortical thickness in the lateral temporal lobe, including the planum temporale (PT), have been reported in MRI studies of schizophrenia (SCZ) and bipolar disorder (BPD) patients. Most of these studies have used a single-valued global or local measure for thickness. However, additional and complementary information can be obtained by generating Labelled Cortical Depth Maps (LCDMs), which are distances of labeled gray matter voxels from the nearest point on the gray/white matter (inner) cortical surface. Statistical analyses of pooled and censored LCDM distances reveal subtle differences in PT between SCZ and BPD groups from data generated by Ratnanather et al. (Schizophrenia Research, http://dx.doi.org/10.1016/j.schres.2013.08.014). These results confirm that the left PT (LPT) is more sensitive than the right PT in distinguishing between SCZ, BPD and healthy controls. Also confirmed is a strong gender effect, with a thicker PT seen in males than in females. The differences between groups at smaller distances in the LPT revealed by pooled and censored LCDM analysis suggest that SCZ and BPD have different effects on the cortical mantle close to the gray/white matter surface. This is consistent with reported subtle changes in the cortical mantle observed in postmortem studies.